Student’s Perception About Using Youtube Educational Video in Learning Vocabulary - Wulandari, Yolanda; Sain, Yuliyanah; Aradhawaty , Syenja (Institut Agama Islam Negeri Palopo, 2025)
The purpose of the study was to determine students' perception of the use of YouTube educational videos in learning English vocabulary. The research method used is qualitative and the sample in this study is 6 grade XI students of SMKN 10 South Konawe who were selected based on their habits in using YouTube as an English learning medium. Data were collected through semi-structured interviews to explore the experiences, benefits, and challenges faced by students in learning vocabulary using YouTube. The results showed that all participants responded positively to the use of YouTube as a vocabulary learning medium. Based on these findings, YouTube can be an effective learning tool in improving English vocabulary mastery. Teachers are advised to integrate YouTube educational videos in classroom learning to increase students' interest and understanding of English.